Rawls’s Justice as Fairness and Indonesian Health Policy: A Doctrinal Framework for Equity-Oriented Reform - Tony Richard Alexander Samosir; Mei Susanto (JUSTISI, 2026)
The study aims to analyze the application of John Rawls' Theory of Justice in Indonesia's health system policy, emphasizing how principles of justice can promote fairness and equality in the provision of health services, especially for disadvantaged populations.The method used was a judicial normative (doctrinal) approach. This study critically reviewed legal and philosophical texts relevant to the Indonesian health policy framework, integrating Rawls' theory as an analytical lens.The novelty of this research lies in the operationalization of Rawls' abstract philosophical principles into a structured evaluation framework (Rawlsian grid) and its application to the Indonesian socio-political and cultural context. This allows for a systematic assessment of inequalities in the health system and proposals for equitable policy solutions.The findings show that programs such as the National Health Insurance Scheme (JKN) have contributed to broader access to health care, but disparities remain in remote and underdeveloped areas. Using the Rawlsian grid, the study highlights challenges in budget allocation, health worker distribution, and infrastructure access. Recommended strategies include reallocating health budgets, fair distribution of health workers, expansion of telemedicine, and participatory planning.The concludes that integrating Rawlsian principles of justice through a structured evaluation framework can support a more inclusive and sustainable health system in Indonesia, ensuring fair and equal access to quality health services for all citizens.